2008
DOI: 10.1002/anie.200705648
|View full text |Cite
|
Sign up to set email alerts
|

α‐MnO2 Nanowires: A Catalyst for the O2 Electrode in Rechargeable Lithium Batteries

Abstract: Higher‐capacity lithium batteries can be fabricated by using α‐MnO2 nanowires as the catalyst in a porous, composite oxygen cathode. In the depicted scanning electron micrograph of a composite positive electrode, deposits of Li2O2, which accumulates during discharge, can be seen within a porous matrix consisting of α‐MnO2 and carbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
793
4
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 895 publications
(821 citation statements)
references
References 12 publications
20
793
4
4
Order By: Relevance
“…The Bruce group have investigated the effect of various catalysts on electrochemical performance. [ 41 ] [ 42 ] Among them, α -MnO 2 nanowires showed the best electrochemical performance, delivering about 3000 mAhg − 1 at a current density of 75 mAg − 1 , and showing a stable cycle performance for 10 cycles ( Figure 4 ). This group suggested that the improvement is due to the crystal structure having 2 × 2 tunnels formed by edge-and corner-sharing MnO 6 octahedra.…”
Section: Catalystmentioning
confidence: 99%
“…The Bruce group have investigated the effect of various catalysts on electrochemical performance. [ 41 ] [ 42 ] Among them, α -MnO 2 nanowires showed the best electrochemical performance, delivering about 3000 mAhg − 1 at a current density of 75 mAg − 1 , and showing a stable cycle performance for 10 cycles ( Figure 4 ). This group suggested that the improvement is due to the crystal structure having 2 × 2 tunnels formed by edge-and corner-sharing MnO 6 octahedra.…”
Section: Catalystmentioning
confidence: 99%
“…27,28 Rutile MnO 2 , particularly in nanowire form, has been demonstrated to reduce overpotentials and improve the cycling stability of the Lioxygen system. 8,29 Recent studies, however, have emphasized the presence of electrolyte decomposition in these earlier works, making the efficacy of catalysts less clear. 30−33 Nevertheless, with more recent demonstrations of the Li−O 2 system being cycled with good electrolyte stability 34,35 it is likely that the role of catalysts will become a focus of future studies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although the specific chemistry of the physical structure residing at the cathode (the "air electrode") can be varied, it must be structurally sound, conductive, and effectively catalyze the oxygen reduction reaction. Typically, a composite comprising a conductive material physically mixed with an oxygen reduction catalyst is utilized, often integrated with binder 10,11 and a metal mesh as support. 32,33 Thus, the conventional approach to air electrodes positions catalyst particles randomly throughout the thickness of the composite electrode, analogous to the positioning of active material particles within a conventional battery electrode (Fig.…”
Section: Metal Air Cathodesmentioning
confidence: 99%